Signal transduction pathway mediated by the novel regulator LoiA for low oxygen tension induced Salmonella Typhimurium invasion - Jiang, Lingyan; Feng, Lu; Yang, Bin; Zhang, Wenwen; Wang, Peisheng; Jiang, Xiaohan; Wang, Lei (PLoS pathogens, 2017)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is a major intestinal pathogen of both humans and animals. Salmonella pathogenicity island 1 (SPI-1)-encoded virulence genes are required for S. Typhimurium invasion. While oxygen (O2) limitation is an important signal for SPI-1 induction under host conditions, how the signal is received and integrated to the central SPI-1 regulatory system in S. Typhimurium is not clear. Here, we report a signal transduction pathway that activates SPI-1 expression in response to low O2. A novel regulator encoded within SPI-14 (STM14_1008), named LoiA (low oxygen induced factor A), directly binds to the promoter and activates transcription of hilD, leading to the activation of hilA (the master activator of SPI-1). Deletion of loiA significantly decreased the transcription of hilA, hilD and other representative SPI-1 genes (sipB, spaO, invH, prgH and invF) under low O2 conditions. The response of LoiA to the low O2 signal is mediated by the ArcB/ArcA two-component system. Deletion of either arcA or arcB significantly decreased transcription of loiA under low O2 conditions. We also confirmed that SPI-14 contributes to S. Typhimurium virulence by affecting invasion, and that loiA is the virulence determinant of SPI-14. Mice infection assays showed that S. Typhimurium virulence was severely attenuated by deletion of either the entire SPI-14 region or the single loiA gene after oral infection, while the virulence was not affected by either deletion after intraperitoneal infection. The signal transduction pathway described represents an important mechanism for S. Typhimurium to sense and respond to low O2 conditions of the host intestinal tract for invasion. SPI-14-encoded loiA is an essential element of this pathway that integrates the low O2 signal into the SPI-1 regulatory system. Acquisition of SPI-14 is therefore crucial for the evolution of S. Typhimurium as an intestinal pathogen.